Effect of intermittent voltage source converter faults on the overall performance of wind energy conversion system - Abdou, A.; Abu-Siada, Ahmed; Pota, H.R. (Taylor & Francis, 2013)
The doubly fed induction generator (DFIG) is interfaced to the AC network through voltage source converters (VSCs) which are considered to be the core of the DFIG system. This paper investigates the impact of different intermittent VSC faults on the overall performance of a DFIG-based wind energy conversion system (WECS). The fault ride through capability of the DFIG under various VSC faults is also investigated. Faults such as open circuit and short circuit across the switches, when they occur within the grid side converter (GSC) and rotor side converter (RSC), are considered and compared in this paper. Short circuit and open circuit across the DC-link capacitor are also considered in this study as common VSC problems. Simulation results indicate that the short circuit faults have a severe impact on the overall performance of the DFIG, especially when they occur within the GSC. This is attributed to the fact that the GSC directly regulates the point of common coupling voltage. The open circuit faults have less impact on the performance of the DFIG-based WECS. A proper controller along with flexible AC transmission device should be available to compensate the required active and reactive power during these faults. A protection technique is necessary to detect these faults in advance to protect the VSC switches and the machine winding from any catastrophic failure.